Flexural behavior of concrete-filled rectangular steel tubular (CFRST) trusses. (February 2022) - Ma, Yinping; Liu, Yongjian; Wang, Kun; Ma, Tianyu; Yang, Jian; Liu, Junping; Gao, Yimin; Li, Hui
Abstract: Concrete filled rectangular steel tubular (CFRST) trusses are composed of CFRST chords and rectangular hollow section (RHS) braces. To analyze the flexural behavior of CFRST trusses, a series of 10 experiments were re-analyzed. Effects of infilled concrete and longitudinal perfobond leister (PBL) stiffeners in the chords were investigated. Experimental results indicated that the flexural stiffness and strength of the CFRST trusses were improved significantly compared to the RHS trusses. Joint strength of the trusses was enhanced by infilled concrete under compression and PBL stiffeners under tension. The failure modes of the truss were changed after the joints were strengthened. Axial force distribution of the truss members coincided well with pin-jointed analysis results. Axial stiffness of the CFRST chords under tension and compression was investigated. Furthermore, an approach to determine the flexural strength of the CFRST trusses was introduced and validated against the experimental results. The efficient factors of the truss members which can be used as indexes for optimal design were proposed.